Experimental Investigation on Thermal Performance Optimization of Na2HPO4·12H2O-Based Gel Phase Change Materials for Solar Greenhouse - Wenhe Liu; Gui Liu; Wenlu Shi; Xinyang Tang; Xuhui Wu; Jiayang Wu; Zhanyang Xu; Feng Zhang; Mengmeng Yang (Gels)
The content of modified materials in multicomponent gel phase change materials directly affects their performance characteristics. To investigate the influence of different contents of modified materials on the performance features of Na2HPO4·12H2O-based multicomponent Gel Phase Change Materials, four single factors (Na2SiO3·9H2O, C35H49O29, KCl, and nano-α-Fe2O3) and their interactions were selected as influencing factors. Using the Taguchi method with an L27(313) orthogonal array, multi-step melt–blending experiments were conducted to prepare a novel multi-component phase change material. The characteristics of the new multi-component phase change material, including supercooling degree (ΔT), phase change temperature (Tm), latent heat of phase change (ΔHm), and cooling time (CT), were obtained. In addition, characterization techniques such as DSC, SEM, FT-IR, and XRD were employed to analyze its thermal properties, microscopic morphology, chemical stability, and crystal structure. Based on the experimental results, the signal-to-noise ratio (S/N) was used to rank the influence of each factor on the quality characteristics, and the p-value from analysis of variance (ANOVA) was employed to evaluate the significance of each factor on the performance characteristics. Then, the effects of each significant factor on the characteristics of the multiple gel phase change materials were analyzed in detail, and the optimal mixing ratio of the new multiple gel phase change materials was selected. The results showed that Na2SiO3·9H2O, KCl, and α-Fe2O3 were the most critical process parameters. This research work enriches the selection of composite gel phase change materials for solar greenhouses and provides guidance for the selection of different modified material contents using Na2HPO4·12H2O as the starting material.